Caught In the Net: Narrative Style 2d Animation on Advertising Awareness Campaign on The Effects of Social Media Towards Adolescent Development - Mohd Nazley, Naqhib; Mohd Ismazi Effendy, Izudin Zikry; Jayakumar, Marthiiny; Mohd Herrow, Mohd Firdaus (Multidisciplinary Applied Research and Innovation, 2024)
Adolescence is a crucial stage in life, and social media has become a prevalent and extensively used activity among teenagers due to advancements in technology. Popular platforms such as Facebook, Twitter, YouTube, Instagram, and TikTok dominate their daily routines. Unfortunately, the detrimental effects of social media on adolescents often go unnoticed. This project aims to address the negative influences of social media on teenagers, specifically focusing on three key issues they face: sleep deprivation, low self-esteem, and the fear of missing out. Additionally, the project aims to conduct a study on the foundational aspects of adolescent development in relation to the impact of social media on their growth. It also involves creating a 2D animated narrative that depicts the effects of social media usage on adolescent development, and analyzing the effectiveness of a 2D animated advertising campaign in promoting awareness and understanding of this issue. To gather data, both primary and secondary sources will be utilized, including interviews, surveys, journal articles, and internal records. The project's objective is to raise awareness about the importance of fostering productive teenagers during their developmental years. By the project's completion, we hope to educate the public about the negative consequences of excessive social media use on adolescent growth and encourage preventive measures to mitigate this situation.